Pengaruh Beban Pajak Tangguhan Dan Perencanaan Pajak Terhadap Manajemen Laba Pada Perusahaan Manufaktur (Subsektor Kimia) Yang Terdaftar Di BEI Tahun 2019-2023 - Jonnedi Jonnedi; Muhammad Yusuf; Menhard Menhard; Giri Suseno (Sekolah Tinggi Ilmu Ekonomi Mahaputra Riau, 2026)
The purpose of this study is to determine the effect of deferred tax burden and tax planning on earnings management in manufacturing companies (chemical sector) listed on the Indonesia Stock Exchange in 2019-2023. The research method used in this study is a quantitative method. The type of data used is secondary data. The population in this study amounted to 11 companies. Based on the predetermined criteria using purposive sampling technique, 9 companies were obtained. The analysis techniques used are descriptive statistical analysis, multiple linear regression analysis, classical assumption test and hypothesis test, then processed using the SPSS 2023 application. The results of this study indicate that partially deferred tax burden affects earnings management and tax planning affects earnings management. Simultaneously deferred tax burden and tax planning affect earnings management.